2021
DOI: 10.1007/s13201-020-01346-5
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic, equilibrium and thermodynamic studies of the adsorption of paracetamol in activated carbon in batch model and fixed-bed column

Abstract: This work studied the removal of paracetamol through the adsorption process using the granular activated carbon. The results indicated that it was possible to obtain 95% of removal under the experimental conditions of pH 6, 120 min of process and 5 g L−1 of solid adsorbent. The kinetic model that best fit the experimental data was the pseudo-first order. The isotherm model that best fit the experimental data was the Sips. The thermodynamic tests indicated that the adsorption process was favorable and spontaneo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 26 publications
1
18
0
Order By: Relevance
“…In their study of adsorption of Paracetamol with commercial activated biochar, Haro et al, (2021), obtained 95% removal for 120 min with a concentration of 5 g L -1 , a result close to that obtained in the present study. In their investigation on the potential of adsorption of the grape stalk biochar on Paracetamol (20 mg L -1 ), Villaescusa et al, (2011) obtained a removal of 30%, a percentage lower than that identified in this work when comparing the concentration of the pollutant.…”
Section: Biochar's Efficiency In Removing Pollutantssupporting
confidence: 90%
See 1 more Smart Citation
“…In their study of adsorption of Paracetamol with commercial activated biochar, Haro et al, (2021), obtained 95% removal for 120 min with a concentration of 5 g L -1 , a result close to that obtained in the present study. In their investigation on the potential of adsorption of the grape stalk biochar on Paracetamol (20 mg L -1 ), Villaescusa et al, (2011) obtained a removal of 30%, a percentage lower than that identified in this work when comparing the concentration of the pollutant.…”
Section: Biochar's Efficiency In Removing Pollutantssupporting
confidence: 90%
“…The adsorbent saturates slowly, causing an increase in the saturation time. Haro et al, (2021) demonstrated the removal of Paracetamol by adsorption in activated biochar, and identified the same behavior regarding the saturation time, the higher the concentration of the pollutant, the greater the saturation time.…”
Section: The Breakthrough Curves Of Methylene Blue and Paracetamolmentioning
confidence: 60%
“…This could be due to the stronger electrostatic interaction mechanisms involved in the uptake of the dye species in comparison to the weaker H-bonding and Van der Waals forces predominant in paracetamol adsorption. Moreover, the adsorption of paracetamol on CuONPs is higher than that obtained for other efficient adsorbents like sugar cane bagasse (0.121 mg/g) 60 , metal–organic-framework-MIL type (1.87 mg/g) 61 , activated carbon (43.5 mg/g) 62 and acid modified clay (43.92 mg/g) 20 . Similarly, the uptake of thiazolyl blue on the CuONPs was higher than 48.80 mg/g reported for American sycamore derived biochar 14 .…”
Section: Resultsmentioning
confidence: 72%
“…The observance of a plateau in the later phase was due to the adsorption of PCT on internal binding sites in the pores of f-PKHN, which used a relatively greater time than external active sites of f-PKHN. Various adsorbents used for PCT removal, such as innovative spherical biochar (120 min), 5 granular activated carbon (120 min), 49 and cotton cloth residue activated carbon (60 min) 50 depicted a higher contact time than the synthesized hydrogel nanocomposite (25 min) that substantiated f-PKHN as an advanced and economical adsorbent.…”
Section: Resultsmentioning
confidence: 95%